Pacing strategy adopted in crawl swimming competitions: an analysis of the 800-m and 1500-m distances - Mayara Vieira Damasceno; Carlos Rafaell Correia-Oliveira; Thais Narita; Leonardo Alves Pasqua; Salomão Bueno; Adriano Eduardo Lima-Silva; Rômulo Bertuzzi (Universidade Federal de Santa Catarina, 2013)
In long distance swimming competitions, the optimal pacing strategy is not well established. The objective of this study was to characterize the pacing strategy adopted by international level athletes in 800-m (female) and 1500-m (male) crawl swimming events. We analyzed the time of each 50 m splits for semi-finalists and finalists athletes of the last three world swimming championships from 2006 to 2010. The data analysis was performed through the statistic method named CHAID (Chi-Squared Automatic Interaction Detection), which is a statistic χ2 to detect a homogeneity behavior among the variables. The main results found were: for the two events analyzed, the velocity-versus-distance curve was similar to the parabolic pacing strategy (U-shaped), characterized by a significantly faster start (p<0.05) than mean velocity for the race, followed by a gradual decline invelocity in the middle splits, when athletes increase the velocity again (p<0.05) to produce an end spurt. In conclusion, these findings indicate that this pacing strategy profile can be classified as optimal for the long distances wimming events since it was preferentially adopted by international level athletes.